SEMANTIC FEATURES OF ABSTRACT NOUNS WITH THE DEIXIS VALUE FORMED BY THE MODEL ROOT OF THE WORD + SUFFIX -OVINA - Irina N. Korsunova (Вестник Северо-Кавказского федерального университета)
The article considers a number of nouns certain word-building models, which are widespread in the modern Russian language; identify typological features of these tokens